Design and Evaluation of Livestock Feed Chopper Machine - Pai, Angela Wetron; Senawing, Kasmawati; Nor, Fethma M (Journal of Applied Science, Engineering and Technology, 2021)
Nowadays in Malaysia, the livestock industry has become the increasing demand over the past few years. Like agriculture, livestock is also a growing business that can help local farmers to generate their income. Thus, an economic and practical chopper machine for livestock feed is necessary to fulfil this demand. The machine is driven by an AC powered motor (1400 rpm, 1 Hp). It is divided into five major components, which are the fodder inlet, fodder outlet, power unit, cutting unit and frame stand. For safety reason, a cover made by clear acrylic Perspex were built in front of the blade to prevent any injuries. The machine structure is reasonable and practical as it is supported by four lockable wheels and handle for easy movement. Time taken to finish the chopping process will be analyzed for both methods. Three different weights of fodder will be used. For 500g, 1000g and 1500g of weight, average production time taken by machine is 15s, 33s and 42s respectively. While conventional method is 240s, 400s and 640s respectively. The percentage decrease of production time was calculated to evaluate the performance. Based on the result obtained, it shows that by using the chopper machine, it can help to reduce the production time to produce the chopped fodder compared to the conventional method. For weight 500g, it reduces the production time to 93.75%, for weight 1000g to 91.75% and lastly for weight 1500g to 93.44%. Hence, the chopper machine is practical, flexible and cost effective to use for chopping fodder.